Advances on Statistical Methods in Engineering, Science, Economy, Education and Disaster Management - Primatika, Roza Azizah (Universitas Islam Indonesia, 2015)
Fish is a source of animal protein needed by the human body. The excess of fish in the harvesting moment can cause economic loss for the fisherman if not directly sold out. Fish preservation is needed but it need long time and difficult to apply in the small scale fisherman, it cause the fisherman choose formaldehyde as illegal food preservation chemical to avoid spoilage process in the fish. The aim of the present study was to determine the formaldehyde content in the jambal roti salted fish using Schiff solution and risk factor on sales location of jambal roti salted fish. A total of 32 samples of jambal roti salted fish were taken from several traditional markets and supermarkets in Yogyakarta. All of samples were analyzed using Schiff solution to detect the content of formaldehyde in jambal roti salted fish. All of data were analyzed by descriptive and inferential. Descriptive analysis results showed that 64.7% (11/17) samples of jambal roti salted fish came from traditional markets were positive detected formaldehyde and 35.3% (6/17) samples were negative. While the samples came from supermarket shows that 60% (9/15) were positive detected formaldehyde and 40% (6/15) samples were negative. The Chi-Square test was performed to determine the risk factor for the sales location of jambal roti salted fish based on the descriptive analysis data. Chi-square test showed that no statistically significant association between the sales location and detection of formaldehyde in jambal roti salted fish (pvalue>0.05). However, the traditional markets have risk 1,222 times to have positive detected formaldehyde than Supermarket (OR = 1.222).